Características agronômicas, adaptabilidade e estabilidade produtiva de genótipos de quinoa - Egewarth, Vanessa Aline (2016)
The consumption of quinoa is growing in the world because of its high nutritional value and genetic variability and may be an alternative for the diversification of production, however studies in culture are still restricted to the Cerrado region, making it necessary to provide cultivars adapted to southern Brazil . This study was conducted in order to characterize and analyze the adaptability and stability quinoa Willd genotypes belonging to the Quinoa Improvement Program, State University of Paraná West - UNIOESTE. Four experiments were conducted three of them in the experimental field of Entre Rios do Oeste and one in Rondon. The experimental design was randomized blocks, composed of thirteen (only the first experiment) and sixteen genotypes of C. quinoa selected within populations of Royal Quinoa, Cherry Vanilla, Brilliant Rainbow Quinoa and Orange, in three replications. The parameters evaluated were: number of days to flowering, plant height at flowering, cycle, plant height at maturity, the first inflorescence insertion height, plant population, productivity, saponin content and moisture. the methodologies were used: Eberhart and Russell, Lin and Binns, adapted by Aries, and the Integrated Method for determination of stability and phenotypic adaptability productivity. Plant height at flowering ranged from 0.75 to 1.09 m, and 0.80 to 0.91m in the experiments, respectively. In the first experiment the Q13-17 genotype with higher productivity, only took 46.57 days after sowing to flower, and time below the eleven genotypes. All genotypes are considered bitter, presented early cycle and height of the first inflorescence enough to allow mechanized harvesting. The Q13-04 genotypes, Q13-20, Q13-21, Q13-24 and Q2014 were classified as stable by the methods proposed by Eberhart and Russell and Lin and Binns adapted by Carneiro. There was agreement between the methods of Eberhart and Russell and Integrated for Q13-01 genotypes, Q13-06, Q13-10, Q13-18 and Q13-20, which have high adaptability to the environments studied. All methods showed the Q13-02 genotype as the least adaptability and phenotypic stability, which is subject to disposal quinoa Improvement Program. The Q13-04, Q13-06 genotypes, Q13-17, Q13-21 and Q2014 have agronomic characteristics such as yield potential, early cycles, and time of the first inflorescence enough to allow mechanized harvesting, as well as stability and phenotypic adaptability to environmental conditions the Western Region of Paraná and may be released as new varieties adapted to areas with environmental conditions similar to the study